2022
DOI: 10.1101/2022.05.31.494146
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacological PP2A reactivation overcomes multikinase inhibitor tolerance across brain tumor cell models

Abstract: Background: Glioblastoma is characterized by hyperactivation of kinase signaling pathways. Regardless, most glioblastoma clinical trials targeting kinase signaling have failed. We hypothesized that overcoming the glioblastoma kinase inhibitor tolerance requires efficient shut-down of phosphorylation-dependent signaling rewiring by simultaneous inhibition of multiple critical kinases combined with reactivation of Protein Phosphatase 2A (PP2A). Methods: Live-cell imaging and colony growth assays were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 51 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…Our own lab's contribution to uncovering the role of mitochondria in cancer therapy tolerance also comes from studies of brain tumor cells. Following previous findings demonstrating potent synthetic lethality in GB cells by multikinase inhibition and PP2A reactivation [14], we recently demonstrated that the critical kinase targets for this synthetic lethal phenotype were AKT and mitochondrial pyruvate dehydrogenase kinases (PDKs) [15]. Across heterogenous GB and medulloblastoma (MB) cell models, none of the combinations of two compounds from AKT inhibitor (AKTi), PDK inhibitor (PDKi), or PP2A reactivator (PP2Aa) induced cell killing across all cell models, whereas this was observed in all cell models with the AKTi + PDKi + PP2Aa triplet therapy.…”
Section: Figmentioning
confidence: 94%
See 4 more Smart Citations
“…Our own lab's contribution to uncovering the role of mitochondria in cancer therapy tolerance also comes from studies of brain tumor cells. Following previous findings demonstrating potent synthetic lethality in GB cells by multikinase inhibition and PP2A reactivation [14], we recently demonstrated that the critical kinase targets for this synthetic lethal phenotype were AKT and mitochondrial pyruvate dehydrogenase kinases (PDKs) [15]. Across heterogenous GB and medulloblastoma (MB) cell models, none of the combinations of two compounds from AKT inhibitor (AKTi), PDK inhibitor (PDKi), or PP2A reactivator (PP2Aa) induced cell killing across all cell models, whereas this was observed in all cell models with the AKTi + PDKi + PP2Aa triplet therapy.…”
Section: Figmentioning
confidence: 94%
“…These findings highlighted that triplet targeting is required to overcome both therapy‐induced adaptation but also the heterogeneity of therapy responses across brain tumor cell populations. Mechanistically, PP2A reactivation blocked compensatory OXPHOS activation by PDKi, and induced mitochondrial proton leakage, whereas the combination of AKTi + PDKi caused widespread BH3‐mediated mitochondrial apoptosis priming [ 15 ]. The significant therapeutic impact of the orally dosed mitochondrial triplet therapy was demonstrated in both GB and MB intracranial models.…”
mentioning
confidence: 99%
See 3 more Smart Citations